Ikhtilat dalam Perspektif Ulama Klasik dan Ulama Kontemporer: Studi Kasus Pengkaderan Basic Training Himpunan Mahasiswa Islam Cabang Gowa Raya - Aqsa, Muh Nur; Sabir, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2023)
Association is the need of every living being, especially humans as social beings who need each other, so that association will occur every day between fellow living beings. Association is a process of interaction carried out by individuals with other individuals, it can also be by individuals with groups. Because human beings are naturally social beings who cannot live alone without other beings, so to meet the needs of life and their interests, humans always live in society. Shari‟at Islam has set good sociability procedures and boundaries in association, both between individuals and groups, both same-sex and opposite-sex. There are strong boundaries in Islamic shari'a. . The purpose of this study is to explore and refer to the law of ikhtilat the perspective of classical and contemporary scholars. The research method used is field research which is qualitative. The data sources used are sourced from primary and secondary data. The result of this study is that Ikhtilat at its origin is allowed by syara', but with some conditions. If not, then it is difficult for human life all day long. However, we need to distinguish between justified and forbidden ikhtilats. Ikhtilat, as we mentioned earlier, the law of origin is mubah (must) to facilitate human life. There is no obstruction to him unless he leads to an illegitimate matter.